2021
DOI: 10.1080/21655979.2021.2004981
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes derived from microRNA-129-5p-modified tumor cells selectively enhanced suppressive effect in malignant behaviors of homologous colon cancer cells

Abstract: Exosome-encapsulated microRNAs (miRNAs) are novel diagnostic and predictive markers in colon cancer. Hence, the study of serum exosomal miRNAs in patients with colon cancer may help its diagnosis and treatment. PKH26-labeled exosomal uptake analysis identified whether exosomes transfer miRNA-129-5p to target cells. Transmission electron microscopy and dynamic light scattering analysis were applied to determine exosome morphology and size distribution. The Cell Counting Kit-8, wound healing assay and Transwell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Specifically, exosomes derived from tumor cells transfected with stable miRNA-129-5p exhibited selective apoptosis induction by decreasing Bcl-2 expression and increasing Bax expression. Additionally, these exosomes mitigated malignant characteristics associated with colon cancer [ 93 ].…”
Section: Exosomal Micrornas In Cancer Apoptosismentioning
confidence: 99%
“…Specifically, exosomes derived from tumor cells transfected with stable miRNA-129-5p exhibited selective apoptosis induction by decreasing Bcl-2 expression and increasing Bax expression. Additionally, these exosomes mitigated malignant characteristics associated with colon cancer [ 93 ].…”
Section: Exosomal Micrornas In Cancer Apoptosismentioning
confidence: 99%
“…Ferroptosis-inducing miRNAs miR-101-3p [27] Medulloblastoma [250] RAB27A miR-1231 [225] Pancreatic ca [251] miR-1287-5p [226] Inflammatory injury [252] RAB7A miR-129-5p [243] Colon ca [253] VPS4B, ATP9A, PDCD6IP miR-142-3p [224] Retinoblastoma [254] STAM, HGS miR-143-3p [212] Lung ca [255], pancreatic ca [256] RAB7A miR-144-3p [234] Endothelial cells [257] VPS4B, PDCD6IP, SMPD3 miR-15a-5p [227] Endometrial ca [258], lung ca [259] MYO5B, VPS4A miR-15a-3p [228] Wound repair [260] miR-19b-3p [242] Lung ca [261] SDC1, VPS4B, MYO5B miR-28-5p [235] Lung injury [262 Ferroptosis-inhibiting miRNAs miR-18a-5p [248] Osteoblast cells [268] miR-19a-3p [21] Ischemic myocardium [269] SDC1, VPS4B, MYO5B miR-23a-3p [244] Cholangiocarcinoma [270] miR-424-5p [245] Endothelial cells [271] VPS4A, MYO5B miR-4291 [246] ATP9A, SMPD3, TSG101, MYO5B miR-522-3p [249] PDCD6IP miR-670-3p [247] CD34, RAB27A…”
Section: Ferroptosis-modulating Mirna Exosomal Mirna Studies Exosome ...mentioning
confidence: 99%
“…Exosomal miRNA-1231 derived from bone marrow mesenchymal stem cells inhibits the proliferation and migration of pancreatic cancer cells [ 251 ]. Exosomal miR-129-5p inhibits the proliferation and migration of colon cancer cells [ 253 ]. Monocyte-derived exosomal miR-142-3p induces the antiproliferation of retinoblastoma cells [ 254 ].…”
Section: Ferroptosis-modulating Mirnas and Their Exosome-biogenesis-t...mentioning
confidence: 99%
“…Numerous studies have demonstrated that sEV-RncRNAs are involved in the regulation of the CRC anti-apoptotic signaling pathway in the tumor microenvironment, thereby inhibiting the proliferation of CRC cells and hindering their development (Nabariya et al, 2020). Ji et al (2021) found that miRNA-129-5p could be delivered to target cells via sEVs to inhibit CRC tumor invasion and migration and promote CRC cell apoptosis. Han et al (2021) found that sEVs loaded with anti-miRNA-221 oligonucleotides were taken up by colon cancer cells through NRP-1 protein and downregulated caco2 and HCT116 in CRC cells, which could inhibit CRC cell proliferation.…”
Section: Inhibit Cancer Cell Proliferation and Promote Apoptosis Of C...mentioning
confidence: 99%